Decisão de investimento: impactos da restrição financeira e das crises econômicas - Kappel, Rodrigo da Silveira (Universidade do Vale do Rio dos Sinos, 2017)
This research investigated the impacts of economic crises on corporate investment decision in Brazilian publicly traded companies, between 1995 and 2015. In order to carry out this research, the companies were separated into two groups to capture the adverse effects of the financial constraint (constrained and unconstrained) and the moderating effect of net assets stocks (higher or lower liquid assets stock). The evaluation of these relationships required the accomplishment of three empirical tests. The results obtained in the first test show that only the payout and size/payout proxies present the behavior recommended by the theory to classify the firms' financial constraint status, reporting results in line with the evidence promoted by Fazzari, Hubbard and Petersen's (1988) basic empirical strategy for investment sensitivity to cash flow. The second test revealed the amplifying effect of economic crises on the investments of Brazilian firms, showing a negative sensitivity of the investment to the cash flow in economic crises periods for the constrained firms, while the investments of unconstrained firms remain insensitive to the flow of in recessive periods. This evidence for unconstrained firms confirms the behavior advocated by the literature, while the amplification of the effect of crises in constrained firms was observed by the negative variation in investment and cash flow in economic shocks times. The results obtained in Brazilian firms are consistent with those evidenced by the theory, considering that the economic crises affect the companies’ investments and the effects are amplified for the constrained firms. In addition, the results of the last test indicate that net assets stocks (cash and cash equivalents; cash and cash equivalents and trade credit – trade accounts receivable; cash and cash equivalents, trade credit – trade accounts receivable and inventory; cash and cash equivalents, trade credit – trade accounts receivable, inventory and trade credit – suppliers; working capital), did not have a damaging effect on the relationships investigated, especially on investments in constrained firms in economic crisis periods. The reported results instigate the continuity of these investigations in order to better understand how the operational and investment adjustments are made, especially in financially constrained companies, either through new proxies to better capture the state of financial constraint, or to construct other variables to expressing the investment, or liquidity, as well as evaluating the impacts with a certain time, lag since an investment decision is virtually irreversible.
Keywords: Investimento; Restrição financeira; Crises econômicas e estoques de ativos líquidos; Investment; Financial constraint; Economic crises and net assets stocks; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis